Population structure of the wood-decay fungus Trichaptum abietinum (J. Dicks.) Ryvarden in the Carpathian National Nature Park (Ukraine) - Boiko, Sergey M. (Biodiversity: Research and Conservation, 2016)
This paper provides a list of intracellular isozyme systems of Trichaptum abietinum (J. Dicks.) Ryvarden (Basidiomycetes) that can be used for population studies. Population structure of the fungus within the Carpathian National Nature Park (CNNP) was established. Percent of polymorphic loci in general was 83.3%. Groups of rare alleles were assigned Sod88, Sod138, Sdh191, and Est111. Calculated Wright's fixation index allowed establishing privilege of the heterozygotes on locus Acp and homozygotes on locus Sod. The population of T. abietinum in the CNNP was in equilibrium state.